EFEKTIVITAS PEMANFAATAN KOMPUTER MUSIK DALAM MANAJEMEN PEMBELAJARAN SENI MUSIK PADA SEKOLAH MENENGAH PERTAMA NEGERI 13 YOGYAKARTA TAHUN AJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The reserach aimed to describe about (1) How management of music education learning in SMP Negeri 13 Yogyakarta whit music computer media?; (2) what are the advantages, disadvantages, and difficulties of school in the implementation of music education learning with computer media? This research used qualitative descriptive method. Data were collected by observation, interviews , and documentation studies. Sources of data consists of informant is the principal, head of administration, music theacer and student.Validity of data used method and data triangulation. The analysis results of this research shows 1) implementation of music education learning with music computer was doing in SMP 13 Yogyakarta, but still used as supplementary tool not as fundamentally tool; (2) The effectivety is achieved through the formulation of curriculum, and the use of music computer media with software encore 45 and cakewalk 9 for supporting learning process. Using music computer make teaching activity more easier for context enrichment topic and utilization makes learning activity is satisfied, so that they give good appreciation.